Prototipo para monitoreo de variaciones de voltaje en electrodoméstico-refrigerador de la despensa "FLOR DE CAÑA"; parroquia Malacatos - Medina Rivera, Galo Fernando (2023)
The present study targets to develop a voltage monitoring system for electric distribution utilities using web technologies. In the context of electrical distribution firms currently face challenges such as voltage deviation due to things like adverse weather conditions, component wear and tear, and human activity. The project consists of three stages: In the first stage, the pre-experimental, non-invasive type prototype is built and installed parallel to the existing connection. Initial functional and calibration tests are performed using a breadboard and schematic diagrams. The second stage, monitoring software is developed using XP methodology, to determine participants, roles, functional and non-functional requirements, user stories, CRC cards, and architecture modeling elements, including use case diagrams, conceptual models, class diagrams, deployment view, and physical view. The IDEs used include Arduino, Visual Studio Code, frameworks such as Espressif IoT Development with the VSCode extension of PlatformIO, JavaScript, and a Wi-Fi connection of the ESP32 linked to the Firebase NoSQL database, which allows the voltage readings and timestamps to be displayed on the Oled display at the installation site, as well as anywhere there is an internet connection. Finally, in the third stage, the correct operation and calibration between the web application and the prototype built are verified by employing unit, acceptance, black box, and stress tests, obtaining good results. The web application developed facilitated the contrast of the information obtained and the statistical analysis with the use of stored values. With this information, the end user can make effective decisions at the time of preventive-corrective maintenance or better manage energy resources based on the data monitored by the web application. Keywords: Arduino, ESP32, Espressif, IoT, Oled, Software development, Voltage sensor, Voltage monitoring system, Wi-Fi.